2005
DOI: 10.1152/jn.01145.2004
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Depolarization Gradients Along the Somatodendritic Axis of CA1 Pyramidal Cells: A Novel Feature of Spreading Depression

Abstract: The results demonstrate that during SD only specific parts of the dendritic membranes are deeply depolarized and electrically shunted. Somatic impalements yielded near-zero membrane potential (V m ) and maximum decrease of input resistance (R in ) whether the accompanying extracellular negative potential (V o ) moved along the basal, the apical or both dendritic arbors. However, apical intradendritic recordings showed a different course of local V m that is hardly detected from the soma. A decreasing depolariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 29 publications
7
81
2
2
Order By: Relevance
“…Standard surgical and stereotaxic procedures were applied for the placement of recording and stimulating electrodes, as previously described [7,8]. The local anesthetic xylocaine was used additionally for the surgery area.…”
Section: Electrode Implantation Microstimulation and Recordingsmentioning
confidence: 99%
“…Standard surgical and stereotaxic procedures were applied for the placement of recording and stimulating electrodes, as previously described [7,8]. The local anesthetic xylocaine was used additionally for the surgery area.…”
Section: Electrode Implantation Microstimulation and Recordingsmentioning
confidence: 99%
“…Also well known is the tight metabolic coupling between neurons and glial cells (reviewed in Araque et al, 2001), which, in the context of energy shortage, is indicated by the disruption of tissue homeostasis in parallel with the gradual decline of the electrical activity and irreversible injury to neurons on selective blockage of the glial Krebs cycle (Largo et al, 1996). In this process, a rapid loss of excitatory synaptic transmission is followed by the spontaneous development of periinfarct-like waves of spreading depression (SD) (Hossman, 1996;Canals et al, 2005b). Although SD has little impact in normal tissue (Herreras and Somjen, 1993), it kills neurons in brain regions deprived of glial activity according to a spatiotemporal pattern, which closely reproduces the sequence of events in the penumbra of an ischemic focus (Fabricius et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In these brain areas, HCN1 subunits are densely distributed and expressed on the dendritic spines of pyramidal neurons (Magee, 1998;Lörincz et al, 2002;Notomi and Shigemoto, 2004;Nusser, 2009), and are involved in the integration of excitatory synaptic input and thereby influences the excitability of neural network (Magee, 1999;Williams and Stuart, 2003;Oviedo and Reyes, 2005;Tsay et al, 2007). Interestingly, cortical spreading depolarization is more readily provoked in hippocampus CA1 sector and neocortex (Somjen, 2001), and its generation as well as propagation is also greatly dependent on the apical dendrites of pyramidal neurons (Canals et al, 2005;Henning et al, 2005;Takano et al, 2007). Therefore, we speculate that HCN1 channels are potential regulative targets which contribute to the formation of neuronal hyperexcitability after SAH.…”
Section: Introductionmentioning
confidence: 99%